Aspiration, respiratory complications, and associated healthcare resource utilization among individuals with Rett syndrome - Nazia Rashid; Jonathan D. Darer; Charles Ruetsch; Xiaoyun Yang (Orphanet Journal of Rare Diseases)
Abstract Background Individuals with Rett syndrome (RTT) are at high risk for aspiration and also experience high rates of lower respiratory tract infections (LRTI) and respiratory failure (RF). Methods A retrospective comparative cohort analysis was performed among 89 individuals with RTT with and without evidence of aspiration, using EHR structured and abstracted clinical notes data. Individuals with known or suspected aspiration (per clinical documentation) (cases) were compared to controls on aspiration risk factors, RF, LRTI, and hospitalization. Results Of eligible individuals, 25 (28.1%) were aspiration cases. The cumulative rate of RF among RTT individuals with and without aspiration was 60.0% and 6.3%, respectively. Aspiration cases were more likely to have risk factors compared to controls during the 6-month baseline including epilepsy (54.5% vs. 4.5%), dysphagia (40.9% vs. 0%), GERD (31.8% vs. 0.0%), scoliosis (31.8% vs. 4.5%), and vomiting (18.2% vs. 0.0%). Aspiration cases were more likely to have LRTI (50% vs. 5.0%) and ≥ 1 inpatient admissions than non-aspiration controls (75.0% vs. 35.0%) (all p < 0.05). Conclusions Individuals with RTT with known or suspected aspiration are at increased risk of LRTI, RF, and inpatient admissions. Providers should monitor aspiration and institute preventative measures among individuals with aspiration risk factors even in the absence of aspiration symptoms.